An innovative sensor for the electrochemical determination of the new melatonergic antidepressant drug agomelatine. (December 2021) - Fekry, Amany M.; Azab, Shereen M.; Abou Attia, Fekria M.; Ibrahim, Neveen S.; Mohamed, Gehad G.
Highlights: Multiwalled carbon nanotubes /cellulose/tween modified carbon paste electrode. Determination of agomelatine (AGO) in human urine and pharmaceutical dosage forms. Simultaneous determination of AGO and dopamine without any cross interference. Fast response, analysis of samples in a short time and lower limit of detection. Abstract: Multiwalled carbon nanotubes/Cellulose/Tween (MWCNTs/C/T/MCPE) reformed carbon paste electrode (CPE) is utilized as an innovative, easy, and sensitive sensor for the electrochemical determination of Agomelatine (AGO) in bulk solution, urine samples, and pharmaceutical formulation. Measurements were performed by means of voltammetric and electrochemical impedance spectroscopy (EIS) techniques in Britton-Robinson (B-R) buffer of pH 2 vs. (Ag/AgCl) reference electrode. Scanning electron microscopy (SEM) was performed to prove the morphology of the proposed sensor. A linear relationship among the AGO anodic peak current and its concentration was found within two linear ranges from 1.0 × 10 −9 to 0.5 × 10 −6 mol L −1 and from 1.0 × 10 −6 to 5.0 × 10 −4 mol L −1 leading to a limit of detection (LOD) of 5.26 × 10 −10 mol L −1 and a limit of quantification (LOQ) of 1.70 × 10 −9 mol L −1 under optimum conditions. The stability, reproducibility, repeatability, interference and concurrent investigation of AGO drug in the presence of dopamine (DA) have been done with satisfactory outcomes. Also, the determination of AGO in Inspago tablets, urine samples and in the presence of dopamine was performed verifying the high sensitivity and selectivity of the proposed method.